2004
DOI: 10.2105/ajph.94.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tobacco Smoke Exposure on Asthma Prevalence and Medical Care Use in North Carolina Middle School Children

Abstract: Objectives. We sought to determine the effects of exposure to environmental tobacco smoke (ETS) and childhood cigarette smoking on asthma symptoms among middle school children in North Carolina. Methods. During 1999–2000, information was collected from a survey completed by the children. Outcomes of asthma symptom reporting were regressed on tobacco smoke exposures. Results. Children who currently smoked or reported any exposure to ETS were at increased risk of reporting active asthma symptoms. Exposure to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 29 publications
3
36
2
1
Order By: Relevance
“…Our study revealed that (65%) of children were exposed to smoking inside the house. This was in accordance with Jesse et al [43] who added that the associations between asthma symptoms and passive tobacco exposure were stronger than the associations between asthma symptoms and active tobacco exposure. As they explained, the reason may be that those children who are exposed to ETS at home have probably endured more long-term tobacco smoke exposure than those children who actively smoke.…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed that (65%) of children were exposed to smoking inside the house. This was in accordance with Jesse et al [43] who added that the associations between asthma symptoms and passive tobacco exposure were stronger than the associations between asthma symptoms and active tobacco exposure. As they explained, the reason may be that those children who are exposed to ETS at home have probably endured more long-term tobacco smoke exposure than those children who actively smoke.…”
Section: Discussionsupporting
confidence: 91%
“…Different studies found different roles of smoking habits and ETS on asthma: some authors found a lower prevalence or severity of asthma and asthma like symptoms in adult smokers (and this finding was attributed to an effect of selection) and in subjects ETS exposed [36][37][38]; some studies, on the contrary, show an association between smoking and asthma hospitalisation in children [39] and in adults [40], or in accelerating [41] or causing the asthma onset [42,43]. The disagreement among studies was evidently due to difficulties in distinguishing with traditional statistical approaches between causative, protective, selective factors and triggers: therefore the demonstration of the secondary (or trigger) role of smoking is one of the main results that this study obtained with the statistical model used.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the European Lung White Book [1], produced in 2003 by the European Respiratory Society and European Lung Foundation, demonstrates that Ireland has the highest mortality rate in Europe from lung disease. The evidence for a direct association of passive smoking with disease and death is now very strong, both in general [2], and specifically related to respiratory disease [3][4][5][6][7], ischaemic heart disease [8][9][10][11] and cancer [12][13][14]. There is also good evidence of specific molecular mechanisms involved in these relationships [15][16][17].…”
Section: Wt Mcnicholasmentioning
confidence: 99%